Uneven air gap optimization of synchronous machine with permanent rotor magnets - V. V. Kharlamov; Yu. V. Moskalev; A. Yu. Milutin; A. P. Popov (Омский научный вестник, 2023)
The article proposes an approach to determining the uneven air gap of a synchronous machine with prismatic magnets on the rotor, in which the distribution of the normal component of magnetic induction along the inner circumference of the stator core has a shape close to sinusoidal. The calculation of the magnetic field of an electric machine model with the specified geometric dimensions and properties of the element materials is performed in the FEMM program. To solve the optimization problem, the Hook-Jeeves method is used, restrictions are taken into account by the method of penalty functions. As a result of modeling the magnetic field of an electric machine with a calculated optimal uneven air gap, a distribution curve of the normal component of magnetic induction along the inner circumference of the stator is obtained, the average deviation of which from the sinusoidal curve is 4,8 %.